(untitled) (Marketing Journal, 2025)
This article analyzes the role of marketing strategies in developing the foreign economic activities of manufacturing enterprises, particularly in the chemical industry. It highlights that strategic planning, innovation, compliance with international stand ards, and risk management are key factors in enhancing the export potential of enterprises. The study evaluates marketing strategies using specific indicators and ranks them based on weighted coefficients. The results identify the most effective and practi cal strategies, which are recommended for application in the chemical sector. 265